INFLUENCE OF VANADIUM CONTENT IN TI-CR-V ALLOYS ON THEIR HYDROGEN SORPTION PROPERTIES - Medvedeva, N.A.; Skryabina, N.E.; Mironova, A.A.; Kuznetsova, E.F.; Kamenschikov, O.J. (Perm Federal Research Centre Journal, 2017)
In this research the regularity of influence of vanadium content on the sorption capacity of the alloy in relation to hydrogen has been investigated and the efficiency of the use of special additives to improve properties of the alloy with a decrease of vanadium content during reduction has been shown. It has been established that alloys (TiCr1.8)40V60 and (TiCr1.8)40V60+Zr7Ni10 possess nearly identical sorption characteristics. Zr7Ni10 additive improves kinetic properties of Ti-Cr-V alloys if the concentration of vanadium is less than 50 at. %.